Molecular dynamics simulations of viral neuraminidase inhibitors with the human neuraminidase enzymes: Insights into isoenzyme selectivity. Issue 19 (15th October 2018) - Richards, Michele R.; Guo, Tianlin; Hunter, Carmanah D.; Cairo, Christopher W.
Graphical abstract: Highlights: Determination of Km values for a fluorogenic 4MU-NANA substrate with purified NEU1-4 isoenzymes. Inhibition assays of DANA, zanamivir, oseltamivir, and peramivir with purified NEU1-4 isoenzymes. MD simulations of NEU2-4 identify important protein-ligand contacts for DANA and zanamivir. MD simulation of NEU2 and NEU3 identify ordered water important for inhibitor design. Abstract: Inhibitors of viral neuraminidase enzymes have been previously developed as therapeutics. Humans can express multiple forms of neuraminidase enzymes (NEU1, NEU2, NEU3, NEU4) that share a similar active site and enzymatic mechanism with their viral counterparts. Using a panel of purified human neuraminidase enzymes, we tested the inhibitory activity of 2-deoxy-2, 3-dehydro- N -acetylneuraminic acid (DANA), zanamivir, oseltamivir, and peramivir against each of the human isoenzymes. We find that, with the exceptions of DANA and zanamivir, these compounds show generally poor activity against the human neuraminidase enzymes. To provide insight into the interactions of viral inhibitors with human neuraminidases, we conducted molecular dynamics simulations using homology models based on coordinates reported for NEU2. Simulations revealed that an organized water is displaced by zanamivir in binding to NEU2 and NEU3 and confirmed the critical importance of engaging the binding pocket of the C7–C9 glycerol sidechain. Our results suggest that compounds designed to target the human neuraminidases should provide more selective tools for interrogating these enzymes. Furthermore, they emphasize a need for additional structural data to enable structure-based drug design in these systems.